Heat transfer fluid and material selection for an innovative Pumped Thermal Electricity Storage system. (15th March 2018) - Benato, Alberto; Stoppato, Anna
Abstract: Renewable energy sources are essential to cover the current energy demand but, especially wind and solar, have a variable and intermittent nature. Therefore, new large-scale energy storage units need to be built up. Pumped Thermal Energy Storage (PTES) is an innovative way to store energy because it is free of geographical constraints and electricity is stored as sensible heat in two man-made tanks. Despite these positive aspects, PTES suffers of high irreversibility and losses. At this purpose, an innovative plant configuration which adopts an electric heater to convert electricity into thermal energy is proposed. A one-dimensional two phase model for the packed bed is adopted to simulate the performance of the hot and cold storages. Being the PTES working fluid, the storage material and the plant management strategy crucial aspects, in this paper, two heat transfer fluids, nine storage materials and different control strategies are tested. The round-trip efficiency and the specific energy are evaluated while an economic analysis is also performed to compute the plant price per energy unit stored. Highlights: A new Pumped Thermal Electricity Storage system is presented. The plant mathematical model is implemented and tested. Different control strategies and reservoirs discretisation are tested. Nine types of bed storage material and two working fluids are tested. An energy and a cost analysis is performed to determine the best fluid and bed material.